Mapping Exclusive Breastfeeding Coverage And Toddler Stunting Prevalence In Indonesia Based On Web Geographic Information System - Setyawati, Vilda Ana Veria; Herlambang, Bambang Agus (Universitas PGRI Semarang, 2020)
Stunting is a chronic nutritional problem Â in most of developing countries for quite a long time, including Indonesia. In 2018, Indonesia had 30.8% of stunting toddlers, 29.6% in 2017 and 27.54% in 2016. The trend over the last 3 years the prevalence of stunting has increased. The purpose of this research is to map the spread of stunting toddlers and exclusive breast milk coverage in Indonesia. This research is a cross sectional study using secondary data sourced from reporting compiled by the Ministry of Health of the Republic of Indonesia in 2018. WebGIS is used to compile mappings of both variables in each province through the official website of BPS. The results of this study show the information presented in WebGis seen most provinces have a prevalence of stunting in black zones (very high) and exclusive breast milk coverage in red zones (very less met than national targets).